Logistics Perfomance Tracking: a Review - Zapateiro-Altamiranda, Orlando (EFIM Ediciones, 2020)
With the organizational challenges posed by phenomena such as globalization, increasingly demanding clients and the digitalization of products and services, it is necessary to make available to these organizations logistics management models that can respond to such challenges. In that order of ideas and through a review of the analytical literature, the following logistics performance measures are presented: Gunasekaran’s Measurement of Performance Indicators of Strategic, Tactical and Operational Levels; Measurement of Performance Indicators in the processes of the logistics chain; SCOR (Supply Chain Operations Reference) model; and Donald Bowersox’s Logistics Reference Model (LMR), commenting on its main characteristics so that both academics and decision makers in the logistics area within organisations have a cognitive tool that allows them to choose the model that suits their needs. The main fndings are linked to a succinct description of the logistics models, making contributions in the academic and practical areas, encouraging future research to go deeper into these measures of the organizational logistics feld.